Diseño de un sistema de control en máquina de fabricación de mallas de acero electrosoldadas (2019)
The welding process of mesh for reinforcement of concentrates manufactured around the world has been advancing significantly, in such a way that currently fully automated machines already exist and therefore the production and capacity of the companies has managed to increase significantly. In order to achieve these improvements in its systems, the company ALMASA S.A, located in Bogotá, has the purpose of having fully automated systems, this implies the renewal of all its machines. Currently one of its electrowelding machines, has a system of feeding crossbars that work manually, the operator must bring the rod to the position of soldier to continue and finish the process automatically, this makes them appear a series of problems and delays in the production of each batch. Due to the above is born the need to reduce these problems and decrease the production time of each batch, for this it is necessary to make a reform to the machine which consists of the implementation of an automatic feeding system and in turn to unify the system of control of the already existing machine with the control of the part of transversal feeding and of this form to be able to unify all the control of the machine. Through the work we will find the introduction in which the objectives and objectives of the project will be made clear, then a state of the art in which we will talk about the machines for manufacturing the electrowelded mesh through time. Next, you will find the specifications of the design project, which will be obtained from several visits to the facilities of ALMASA S.A where the direct people involved were discussed. After these specifications a chapter is completely dedicated to the characterization of the machine of manufacture of electrowelded mesh in order to make known the systems that are in it and some of its technical characteristics. Finally, we will proceed to talk about the control systems to be implemented, in this case we have the control system of the current machine and the control system of the transversal rod feeding system and finally the work will be recommended.